Accurate method for determining the IF noise in SIS heterodyne receivers - Isaak, K; Withington, S; Yassin, G (Kluwer Academic/Plenum Publ Corp, 2000)
We present a new method to determine the contribution of the IF-amplifier chain to the overall noise performance of an SIS-based receiver. Using simulated I-V and IF power characteristics, we show that the standard method used to date to evaluate the IF noise can underestimate the contribution because of non-negligible curvature in the post-gap SIS I-V characteristic. We demonstrate that the new method is not susceptible to the post-gap curvature, and discuss its benefits and limitations to the accurate and precise evaluation of IF noise contributions.